2016
DOI: 10.1007/s10658-016-0999-2
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic variation and virulence related responses of Ascochyta lentis on lentil

Abstract: Ascochyta blight of lentil (Lens culinaris ssp. culinaris) is caused by Ascochyta lentis. The disease causes severe damage to all aerial parts of the plant and may lead to total crop loss during extremely severe epidemics. To identify qualitative differences in resistance within Australian lentil crops, variation in virulence was examined among 17 isolates of A. lentis on six differential lentil genotypes (ILL7537, ILL5588 (cv. Northfield), ILL6002, ILL5722 (cv. Digger), ILL481 (cv. Indianhead) and CIPA203 (cv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 46 publications
5
39
0
Order By: Relevance
“…It appeared that once the infection structure determined a suitable penetration site, the release of cell wall degrading enzymes and/or secretion of toxins was triggered. Similar findings were observed by Sambasivam et al (2017) and Dadu et al (2018), who identified earlier and stronger H2O2 accumulation in a resistant genotype compared to in a moderately resistant and susceptible genotype in the lentil/A. lentis pathosystem.…”
Section: Differences Among Aggressiveness Traits Between Isolates Frosupporting
confidence: 87%
See 1 more Smart Citation
“…It appeared that once the infection structure determined a suitable penetration site, the release of cell wall degrading enzymes and/or secretion of toxins was triggered. Similar findings were observed by Sambasivam et al (2017) and Dadu et al (2018), who identified earlier and stronger H2O2 accumulation in a resistant genotype compared to in a moderately resistant and susceptible genotype in the lentil/A. lentis pathosystem.…”
Section: Differences Among Aggressiveness Traits Between Isolates Frosupporting
confidence: 87%
“…One leaflet from each of four replicates of each host x isolate interaction was inoculated and incubated as described by Sambasivam et al (2017). Briefly, the leaves from each plant were placed with the abaxial surfaces facing upward in a separate petri dish lined with moist filter paper to provide high relative humidity.…”
Section: Inoculation and Sample Collectionmentioning
confidence: 99%
“…Inoculum was prepared as described in Sambasivam et al (2017) and the mini-dome technique of Chen et al (2005) was used to initiate disease. The disease severity of each isolate on each of the host genotypes was assessed using the qualitative 1–9 scale of Singh et al (1981) at 21 days after inoculation (dai) where; scores of 1 or 3 represented a low disease severity; 5 represented a moderate disease severity without significant stem infection, and 7 or 9 represented a high disease severity with stem lesions that would lead to major difficulties in transpiration, photosynthesis and/or breakage.…”
Section: Methodsmentioning
confidence: 99%
“…Several of these were found susceptible or moderately susceptible to recently detected highly aggressive Australian isolates, with predicted increasing industry reliance on those that remained somewhat resistant, such as PBA Jumbo2 and PBA Harricane XT (Davidson et al, 2016). This will again likely lead to increased selection pressure on the highly variable pathogen population (Nasir and Bretag, 1997b, 1998; Davidson et al, 2016; Sambasivam et al, 2017), to evolve and overcome the relatively few resistance sources upon which the industry is currently reliant.…”
Section: Introductionmentioning
confidence: 99%